Market Risk Disclosure and Investor Behavior in the Iraq Stock Exchange - Bushra Abbas Jasim; Hasna Chaibi (Journal of Accounting Science, 2026)
General background: Risk disclosure is critical for strengthening investor confidence and maintaining financial market stability. Specific background: In Iraq, the importance of transparency is heightened by political instability and limited investor protection, positioning the Iraq Stock Exchange (ISX) as a compelling context for study. Knowledge gap: Most prior research on disclosure and investor response has been conducted in developed or relatively stable emerging markets, leaving the Iraqi setting underexplored and findings inconsistent. Objective: This study investigates the effect of market, credit, liquidity, and operational risk disclosures on investor response in ISX-listed banks. Methods: A sample of 20 banks from 2015 to 2023 was analyzed, with disclosure levels measured using IFRS 7 and statistical testing conducted through regression models and ANOVA. Results: Market risk disclosure shows a significant and positive influence on investor response, stronger than liquidity risk, while credit and operational risk disclosures exhibit weaker effects; banks with higher disclosure levels demonstrate superior ROA, ROE, and market value. Novelty: This represents the first comprehensive empirical evidence on Iraqi banks linking multiple risk disclosure categories with investor response over a long period. Implications: The findings extend the Efficient Market Hypothesis and Information Asymmetry theory and provide practical guidance for regulators, banks, and policymakers.